Matemática e arte: incursões na interdisciplinaridade - Souza, Aguinaldo Robinson de [UNESP]; Marques, Emíla de mendonça Rosa [UNESP]; Breda, Ana Maria (My University, 2012)
The complex analysis is, in actuality, a fundamental mathematical object, given its applicability to various areas of science. This paper proposes a more interesting intertwining of mathematical content to the Visual Arts, through computer graphics. The presentation of aesthetic standards, using the “domain coloring” for viewing a complex function, shows that algebraic and geometric properties can be “colored” which makes its study more human, contextualized, pleasant and dynamic, leading to greater ability to understand, to absorb and to create concepts. This work shows the contribution to the interdisciplinarity to study of mathematics.

A análise complexa é, na atualidade, um objeto matemático fundamental, tendo em vista sua aplicabilidade às mais variadas áreas da Ciência. Este trabalho propõe mais um entrelaçamento interessante desse conteúdo matemático com as Artes Visuais, através da computação gráfica. A apresentação de padrões estéticos, utilizando o método domain coloring para a visualização de uma função complexa, mostra que propriedades algébricas e geométricas podem ser “coloridas”, o que torna o seu estudo mais humano, contextualizado, agradável e dinâmico, possibilitando maior capacidade de entendimento, absorção e, até mesmo, de criação de conceitos. Este trabalho evidencia, mais uma vez, a contribuição da interdisciplinaridade ao estudo da Matemática.
Mathematics and art: diving on Interdisciplinarity
Keywords: Mathematics education; Complex numbers; Visual arts; ICT; Educação matemática; Números complexos; Artes visuais; TIC